Análise de associação genômica para tolerância a seca em milho - Bomfim, Renata Pita (2020)
Drought is one of the most limiting factors for the plant development and crop yield. The identification and understanding of the genetic components associated to drought tolerance are essential to develop new varieties and hybrids tolerant to such stress. In the present study 85 maize inbred lines were evaluated in two locations, under irrigated and water stress conditions. For Genomic Association Analysis between markers and QTLs related to drought tolerance, the lines were genotyped using 8,289 SNP markers. Ten QTLs were found on seven chromosomes related to the effect of drought in corn development. Two QTLs are located in regions including the atg18f and ys3 genes. Eight QTLs are located in genomic regions comprising genetic models, five of them are described to related to biotic and abiotic stresses. The QTLs identified in this work have potential to be used in Marker-Assisted Selection programs for drought tolerance after validation across other sets of germplasm.